2022
DOI: 10.1155/2022/4667117
|View full text |Cite|
|
Sign up to set email alerts
|

Multimodal MRI-Based Radiomic Nomogram for the Early Differentiation of Recurrence and Pseudoprogression of High-Grade Glioma

Abstract: Objective. To evaluate the diagnostic value of multimodal MRI radiomics based on T2-weighted fluid attenuated inversion recovery imaging (T2WI-FLAIR) combined with T1-weighted contrast enhanced imaging (T1WI-CE) in the early differentiation of high-grade glioma recurrence from pseudoprogression. Methods. A total of one hundred eighteen patients with brain gliomas who were diagnosed from March 2014 to April 2020 were retrospectively analyzed. According to the clinical characteristics, the patients were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Recent studies have demonstrated the usefulness of radiomics in predicting molecular subgroups of glioma, such as IDH mutations, [6,18] TP53, [19] and MGMT promoter methylations, [20] as well as the recurrence and pseudo progression of high-grade glioma. [21] And, many studies have shown that IDHwt LGAs with TERTp-mutant status have been shown to have a poor prognosis compared to TERTp-wildtype patients and the presence alone is sufficient for the diagnosis of glioblastoma, IDH wt. [4,[22][23][24] However, prediction of TERTp-mutation before surgery and molecular testing can be challenging, as the image features on CT and MRI scans or the pathologically features may appear similar.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the usefulness of radiomics in predicting molecular subgroups of glioma, such as IDH mutations, [6,18] TP53, [19] and MGMT promoter methylations, [20] as well as the recurrence and pseudo progression of high-grade glioma. [21] And, many studies have shown that IDHwt LGAs with TERTp-mutant status have been shown to have a poor prognosis compared to TERTp-wildtype patients and the presence alone is sufficient for the diagnosis of glioblastoma, IDH wt. [4,[22][23][24] However, prediction of TERTp-mutation before surgery and molecular testing can be challenging, as the image features on CT and MRI scans or the pathologically features may appear similar.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding radiomics, Jing et al were able to differentiate early tumor recurrence from pseudo progression when analyzing 2632 radiomic features (e.g., shape features and intensity) in 118 patients. Their method reached a sensitivity and specificity between 64% and 86% and between 61% and 86%, respectively, in discrimination suspect from post-therapeutic lesions (or TRCE) [ 11 ]. Perfusion-weighted sequences, such as the DSC and DCE, are most widely used as a diagnostic tool for everyday clinical use [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of these tumor mimics is radiation necrosis, observed several months and up to years after radiation therapy, is defined by delayed irreversible damage to blood vessels, leading to ischemic necrosis, demyelination, and hemorrhage [ 9 ]. Pseudo progression is a combination of regional inflammation-associated edema and increased vessel permeability without tumoral cell growth, usually frequently occurring within a few months after the end of radiation therapy [ 10 , 11 ]. As both processes show contrast enhancement within the treatment region, it can be difficult to distinguish therapy-related contrast enhancement of brain parenchyma from tumor recurrence or tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%